ELABORAÇÃO DE OBJETOS DE APRENDIZAGEM POR MEIO DE APLICATIVOS EDUCACIONAIS: ANÁLISE DA FORMAÇÃO PROFISSIONAL DOCENTE (REMUNOM, 2025)
It is essential to foster new knowledge linked to a professional teaching culture in which the           development of teaching materials is established in a more autonomous and contextual way.   When it comes to teaching Portuguese, consolidating pedagogical autonomy involves           increasing access to digital media that provide teachers with content and resources to create            more personalized teaching materials that are suited to the specific needs of their students.             In this sense, given the lack of access teachers have to varied quality teaching materials, as well as the difficulties in understanding the guidelines of the BNCC in order to create            teaching tools based on this document, this work proposal, based on the theoretical             foundations of Bakhtinian dialogism, sets itself the general objective of contributing to             research in the field of applied linguistics through the development of an educational            application that assists in the development of teaching materials for the teaching of     Portuguese language in basic education. The methodology used in the research project          entitled “Educational application for the creation of teaching material for Portuguese as a    mother language”, in which we bring the discussions to this article, was inspired by Design      Thinking, that is, an interactive approach centered on people and problem solutions       (BROWN; WYATT, 2010; BROWN, 2017).  The expected results include the realization of         the students' teaching identity and the app's support for the development of learning          objectives for Portuguese language teaching.